Referentes conceptuales y metodológicos sobre la noción moderna de validez de instrumentos de medición: implicaciones para el caso de personas con necesidades educativas especiales - Montero Rojas, Eiliana (2015)
A general look is taken around the modern concept of validity, with a special focus in psychological and educational tests, with the purpose of presenting an updated discussion and providing conceptual and methodological tools to test developers and users. Regarding validity, the important contributions of Samuel Messick are highlighted, including the notion that establishes that this is a unitary concept, referred to the degree of appropriateness of the interpretations and inferences that are drawn from test scores. The measurement models better known and used currently are mentioned, the Classical Test Theory (CTT), and Item Response Theory (IRT), including the Rasch Model. The topics of DIF (Differential Item Functioning) and equating are also introduced. Finally, some implications of this frame of reference are analyzed in terms of the accommodations that are necessary to implement for persons with special educational needs.